Successful treatment of an AIDS patient with prolonged Mycobacterium avium bacteremia, high HIV RNA, HBV infection, Kaposi's sarcoma and cytomegalovirus retinitis. Issue 2 (February 2020) - Furukawa, Yoshitaka; Hamada, Heiichiro; Kamikawaji, Kazuto; Unoki, Taiji; Inoue, Hiromasa; Tashiro, Yukie; Okamoto, Mika; Baba, Masanori; Hashiguchi, Teruto
Abstract: We report an AIDS patient with a high HIV RNA copy number in the plasma who was successfully treated for prolonged Mycobacterium avium bacteremia and other complications. An HIV-infected patient with high fever, anemia, high alkaline phosphatase, cystic lung lesions, hepatitis B virus infection and Kaposi's sarcoma was referred to our hospital. PCR of the blood revealed Mycobacterium avium bacteremia and the time to blood culture positivity was 8 days. The HIV-1 RNA copy number in the plasma was more than ten million copies/ml and the CD4-positive T cell count was 21 cells/μL. Although the high fever resolved five days after therapy for Mycobacterium avium was started, the fever recurred just before starting anti-retroviral therapy (ART) including dolutegravir. The patient experienced repeated but self-limiting bouts of severe inflammation. Mycobacteremia was intermittently detected up to 79 days, suggesting that the recurrent episodes of inflammation were due to the intermittent dissemination of mycobacteria, and that persistent treatment is needed. Five months after the beginning of ART, the HIV-1 RNA copy number in the plasma was still 28, 000 copies/ml. An HIV drug-resistance test revealed sensitivity to all anti-retroviral drugs. Eleven months after the initiation of ART, the HIV RNA copy number in the plasma decreased to 45 copies/mL and the CD4-positive T cell count recovered to 205 cells/μL. Our case also suggests that dolutegravir can be effective in cases with prolonged high levels of HIV RNA. Our findings emphasize that prompt diagnosis and persistent therapy for mycobacterial infection are important for successful treatment.